Pendapatan Rumah Tangga dari Usaha Ikan Asap pada Masyarakat Pesisir di Desa Malalanda Kecamatan Kulisusu Kabupaten Buton Utara - Riska Riska; Anas Nikoyan; Rosmawaty Rosmawaty (Fakultas Pertanian Universitas Halu Oleo, 2022)
This studied aim to determine the amount of household income obtained from smoked fish business in Malalanda Village, Kulisusu District, North Buton Regency. The time of the research was carried out from February to March 2022 with the number of respondents as many as 20 smoked fish business actors. The research variables measured in this study were the husband's income who helped the smoked fish business and the housewife's income obtained from the smoked fish business. Analysis of the data used is to determine the amount of household income obtained from smoked fish business is to use the formula for calculating household income. The results showed that the monthly household income obtained from smoked fish business in Malalanda Village, Kulisusu District, North Buton Regency was Rp. 5,987,314,-/month.